THE EFFECT OF THE PROBLEM-BASED LEARNING MODEL ON THE NUMERICAL LITERACY ABILITY OF ELEMENTARY SCHOOL STUDENTS - Cucun Sunaengsih; Aah Ahmad Syahid; Zahwa Imala (Jurnal Cakrawala Pendas, 2024)
This research was motivated by elementary school students’ low numeracy literacy ability, especially grade III. The low numeracy literacy of students is caused by students' thinking that mathematics is a complex subject and the selection of learning models that do not develop students' critical thinking skills. Meanwhile, students need good critical thinking and problem-solving skills to answer numeracy literacy questions. This study aims to determine the effect of problem-based learning models on numeracy literacy skills. The research method used in this study is a quantitative method with a quasi-experimental non-equivalent control group design. The samples in this study were grade III A and B students of SD Negeri Sukaraja Wetan I. The research instruments used were numeracy literacy tests, teacher performance observation sheets, and student activity observation sheets. Data analysis techniques used in SPSS version 26 are the t-test, simple linear regression, and N-Gain tests. The results of this study showed the influence of the problem-based learning model on the numeracy literacy ability of elementary school students by 52.8%. In addition, there was a difference in students' numeracy literacy ability, marked by an increase of 41% with the medium category in the experimental class. In contrast, in the control class, there was only an increase in scores of 11% with the low category.